Detection and molecular subtyping of Listeria Monocytogenes isolated from a South African avocado processing facility - Bester, Ingrid Muriel (Stellenbosch : Stellenbosch University, 2011)
Thesis (MSc Food Sc)--Stellenbosch University, 2011.